PERBEDAAN GAYA BELAJAR SISWA SERTA KONTRIBUSI BIMBINGAN KONSELING DI MADRASAH MASYARIQUL ANWAR BANDAR LAMPUNG - Bulantika, Siti Zahra; Sari, Rizka Puspita; Dewantari, Tri (Jurnal Inspirasi Bimbingan dan Konseling (JGCI), 2020)
Elementary education or elementary school is the first step for children to improve their abilities, it is from elementary school that they get learning immunity which then becomes a habit they do in the future. Learning style is a way that someone usually uses to absorb and process information from their environment. Based on sensory preferences, students' learning styles consist of visual, auditory, and kinesthetic learning styles. This study aims to determine the learning styles of grade VI students at Madrasah Masyariqul Anwar Bandar Lampung. This research was conducted in March 2020. This study aims to improve students' learning styles with learning achievement. This type of research is observation and interviews. The steps involved in the interview determine the research questions to be answered in the interview. And based on the results of this study that the importance of teachers knowing their learning styles and student achievement in each subject.